Pengaruh Kebiasaan Beribadah, Gemar Belajar dan Kemampuan Bermasyarakat dari Tujuh Kebiasaan Anak Indonesia Hebat Terhadap Sikap Sosial Siswa Kelas XI di SMK Negeri 2 Tana Toraja - Tandilawa, Altin Rimpun; Elpisah, Elpisah; Syarifuddin, Syarifuddin (CV. Rayyan Dwi Bharata, 2026)
This study aims to: 1. To determine and analyze the influence of diligent worship from the Seven Habits of Great Indonesian Children on the social attitudes of Grade XI Accounting Students at SMK Negeri 2 Tana Toraja. 2. To determine and analyze the influence of the Love of Learning from the Seven Habits of Great Indonesian Children on the social attitudes of Grade XI Accounting Students at SMK Negeri 2 Tana Toraja. 3. To determine and analyze the influence of the Social Skills from the Seven Habits of Great Indonesian Children on the social attitudes of Grade XI Accounting Students at SMK Negeri 2 Tana Toraja. 4. To simultaneously determine and analyze the influence of diligent worship, love of learning, and social skills from the Seven Habits of Great Indonesian Children on the social attitudes of Grade XI Accounting Students at SMK Negeri 2 Tana Toraja This research approach uses quantitative research. The research was conducted on class XI students at SMK Negeri 2 Tana Toraja with the population of this study 122 students sampling technique is Purposive Random sampling each study program is represented by 50% so that the number of samples is 60 with details; automotive 10 people, light vehicle engineering 24 people, heavy equipment engineering 19 people and Accounting 7 people total is 60 class XI students of SMK Negeri 2 Tana Toraja. data collection techniques using questionnaires and data analysis techniques using multiple regression techniques and t-test analysis and F Test using SPSS 26. The results of this study are; The probability value of X1 is 0.000. This value is smaller than 0.05 or the calculated t value is 4.984 t table 1.671 (n-1 = 59 alpha 5%) so it can be concluded that the variable of Worship Habits (X1) has a positive and significant effect on the variable of Social Attitudes of Class XI Students of SMK Negeri 2 Tana Toraja. 1). The probability value of X2 is 0.000. This value is smaller than 0.05 or the calculated t value is 6.994 t table 1.671 (n-1 = 59 alpha 5%) so it can be concluded that the variable of Love to Learn (X2) has a positive and significant effect on the variable of Social Attitudes of Students 2). The probability value of X3 is 0.000. This value is smaller than 0.05 or the calculated t value of 4.569 t table 1.671 (n-1 = 59 alpha 5%) so it can be concluded that the variable of Social Ability (X3) has a positive and significant effect on the variable of Social Attitude 3). The sig. value of the F test is 0.000 at a significance level of 0.05. This value is smaller than 0.05 which indicates that all independent variables consisting of; Worship Habits (X1) Love of Learning (X2) Social Ability (X3) together influence the Social Attitude of Students (Y) of class XI SMK Negeri 2 Tana Toraja.